Delirium in Palliative Care - Bramati, Patricia; Bruera, Eduardo (Cancers, 2021)
Delirium, a widespread neuropsychiatric disorder in patients with terminal diseases, is associated with increased morbidity and mortality, profoundly impacting patients, their families, and caregivers. Although frequently missed, the effective recognition of delirium demands attention and commitment. Reversibility is frequently not achievable. Non-pharmacological and pharmacological interventions are commonly used but largely unproven. Palliative sedation, although controversial, should be considered for refractory delirium. Psychological assistance should be available to patients and their families at all times.